Molecular regulation of cellular iron balance. Issue 6 (7th May 2017) - Recalcati, Stefania; Gammella, Elena; Buratti, Paolo; Cairo, Gaetano
Abstract: Handling a life‐supporting yet redox‐active metal like iron represents a significant challenge to cells and organisms that must not only tightly balance intra‐ and extracellular iron concentrations but also chaperone it during its journey from its point of entry to final destinations, to prevent inappropriate generation of damaging reactive oxygen species. Accordingly, regulatory mechanisms have been developed to maintain appropriate cellular and body iron levels. In intracellular compartments, about 95% of iron is protein‐bound and the expression of the major proteins of iron metabolism is controlled by an integrated and dynamic system involving multilayered levels of regulation. However, dysregulation of iron homeostasis, which could result from both iron‐related and unrelated effectors, may occur and have important pathological consequences in a number of human disorders. In this review, we describe the current understanding of the mechanisms that keep cellular iron balance and outline recent advances that increased our knowledge of the molecular physiology of iron metabolism. © 2017 IUBMB Life, 69(6):389–398, 2017